Recording injuries only during winter competitive season underestimates injury incidence in elite alpine skiers - Alhammoud, M.; Racinais, S.; Rousseaux-Blanchi, M. P.; Bouscaren, N. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Current epidemiological studies in elite alpine skiers are mostly limited to retrospective surveys on in-season injury. The aim of this study was to determine the risk and pattern of injury in elite alpine skiers during the winter competitive season (WCS) and the summer off-season (SOS). European Cup skiers were prospectively followed during 5 complete years. 133 skiers-seasons (79 males, 54 females) completed the study. All acute and overuse injuries that required medical attention were registered, representing a total of 166 injuries. Absolute injury incidence was 124.8 (95% CI [106-145]) injuries per 100 athletes per complete season, and was higher during the WCS compared with the SOS, albeit in a smaller magnitude than expected (relative risk ratio (RR) 1.44 [1.06-1.96]). The absolute incidence of severe injuries (i.e. time loss > 28 days) was twofold higher during WCS compared with SOS (RR 2.19 [1.21-3.95]). Most common injuries during the 2013-2015 seasons were knee followed by back (absolute incidences 56 [38-80] and 20 [10-36], respectively; RR 2.82 [1.42-5.61]), but this difference disappeared after 2015 (absolute incidences 25.6 [15.7-39.6] and 23.1 [13.7-36.5], respectively; RR 1.11 [0.59-2.10]). In summary, we found that 98 (59%) injuries occurred during WCS and 68 (41%) during SOS over five years. These results demonstrate the necessity to record injuries during the entire year to avoid a significant underestimation of the injury incidence. In addition, the current data showed an evolution of injury pattern over time and since previous reports, with back injuries being the main concern along knee joint injuries.